Fabrication of Al/Au hybrid SERS substrate using laser engraving for rapid detection of melamine and its analogues by hand-held Raman spectrometer - Wongwasuratthakul, Puwasit; Aumpalop, Weerada; Chakaja, Chaiwat; Satapornchai, Pemika; Eiamsamut, Ploypailin; Somboonsaksri, Pacharamon; Limwichean, Saksorn; Botta, Raju; Nuntawong, Noppadon; Horprathum, Mati; Houngkamhang, Nongluck (My University, 2024)
Surface-enhanced Raman spectroscopy (SERS), combined with a handheld Raman spectrometer, was utilized for the rapid and highly sensitive detection of melamine and its analogues. The investigation focused on the hybrid micro-nano structures of SERS-active substrates, fabricated by laser engraving aluminum (Al) sheets and depositing gold (Au) nanoparticles using magnetron sputtering. The laser engraving frequency was varied to get optimum SERS substrate. The fabricated SERS substrates were tested with rhodamine 6G (R6G) to optimize the Raman signal and subsequently detect melamine and its analogues viz., cyanuric acid, ammeline, ammelide in milk samples. The results demonstrated that a laser frequency of 20 kHz was the optimal condition for fabricating a micro-nano Al template with a depth of 61.21 μm, providing the highest Raman signal for R6G. The limit of detection (LOD) for melamine in mild acid solution and milk samples were determined to be 1x10-5 M and 1x10-4 M, respectively. The laser-engraved Al sheet technique offers a cost-effective approach for SERS substrate fabrication. The integration of the Al/Au hybrid SERS substrate with a hand-held Raman spectrometer demonstrates significant potential for detecting melamine and its analogues in realistic environments.
Keywords: Ammelide; Ammeline; Cyanuric acid; Hand-held Raman spectrometer; Melamine; Surface enhanced Raman spectroscopy